Functionalized UiO-66-NH2 by trimellitic acid for highly selective adsorption of basic blue 3 from aqueous solutions - Wang, Tingting; Han, Lin; Li, Xin; Chen, Tianen; Wang, Shifeng (Frontiers in Chemistry, 2022)
A novel metal-organic framework (MOF) UiO-66-TLA (UiO-66-Trimellitic Acid) was synthesized by one-pot method with trimellitic acid as modifier, which can effectively remove the basic dye Basic Blue 3 (BB3) in wastewater. Modification with carboxyl groups facilitates the adsorption of the cationic dye Basic Blue 3. The adsorption of BB3 by the modified UiO-66-TLA was significantly greater than that of its parent MOF. The adsorption capacity of the modified UiO-66-TLA for BB3 (234.23 mg g−1) was 93.2% higher than that of the original UiO-66-NH2 (121.24 mg g−1), this is closely related to the electrostatic interaction of -COOH in trimellitic acid. UiO-66-TLA was successfully synthesized as indicated by various characterization results. The adsorption kinetics conformed to the pseudo-second-order model, and the adsorption isotherm conformed to the Redlich-Peterson isotherm. This indicates that BB3 is a multi-parameter model of monolayer/multilayer arrangement on the adsorbent surface, and its rate-controlling step is chemisorption. The adsorption process was non-spontaneous and belonged to an endothermic reaction, in addition, it has great adsorption stability and regeneration The interaction of the modified UiO-66-TLA with BB3 was mainly affected by mechanisms, such as electrostatic interaction, π–π stacking as well as the abundant functional groups on UiO-66-TLA surface. These results demonstrate that UiO-66-TLA is an efficient, regenerable, water-stable material for the removal of BB3 in solution, with practical implications, suggesting its potential as a dye adsorbent.